2017
DOI: 10.25125/agriculture-journal-ijoear-jul-2017-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine and ethylene changes during floral initiation in response to paclobutrazol in mango (Mangifera indica L.)

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, few studies investigated ethylene production in leaves, buds, flowers, or other vegetative material from tree crops. Examples are GC detection of ethylene in leaves of citrus (Tudela and Primo- Millo, 1992 ), in shoot portions of apple ( Sanyal and Bangerth, 1998 ), and in floral buds and leaves of mango ( Bindu et al, 2017 ), peach ( Liu et al, 2021 ) and litchi ( Cronje et al, 2022 ) trees. However, most of these studies only provided limited information on the sampling and analysis techniques used to successfully reproduce the techniques for application in other crops with similar plant organs.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies investigated ethylene production in leaves, buds, flowers, or other vegetative material from tree crops. Examples are GC detection of ethylene in leaves of citrus (Tudela and Primo- Millo, 1992 ), in shoot portions of apple ( Sanyal and Bangerth, 1998 ), and in floral buds and leaves of mango ( Bindu et al, 2017 ), peach ( Liu et al, 2021 ) and litchi ( Cronje et al, 2022 ) trees. However, most of these studies only provided limited information on the sampling and analysis techniques used to successfully reproduce the techniques for application in other crops with similar plant organs.…”
Section: Introductionmentioning
confidence: 99%
“…Flowering induction in mango orchards is an agricultural practice carried out on tropical conditions to obtain fruits out-of-season and reach better sale prices. The induc-Morales-Martinez et al: Effect of nitrates alone or with paclobutrazolo on flowering / XXII (2): 20-27 (2020) tion substances regularly applied are potassium nitrate (PN) (Quijada et al, 2008;Sarker and Rahim, 2013;Maloba et al, 2017), ammonium nitrate (AN) (Salazar-García et al, 2000;Silva et al, 2013) and PBZ (Yeshitela et al, 2005;Narvariya et al, 2014;Shinde et al, 2015;Srilatha et al, 2015;Vijaykrishna et al, 2016;Bindu et al, 2017;Narvariya and Singh, 2018), which are applied to improve yield and flowering in the tropics. Several researches have shown that chemical substances are capable to induce flowering in mango.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Upreti et al, (2014) reported increase in carbohydrates as the result of upregulation in certain carbohydrate metabolizing enzymes by paclobutrazol responsible to floral bud initiation in mango. Further, polyaminesethylene balance has been reported by Bindu et al, (2017) crucial for floral bud growth in mango, with high polyamines and reduced ethylene under paclobutrazol contributory to increased flowering.…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%